To simplify the expression \( \frac{56r - 12}{4t} \), we can divide each term in the numerator by the denominator \( 4t \).
-
Start by dividing each term in the numerator by \( 4t \): \[ \frac{56r}{4t} - \frac{12}{4t} \]
-
Simplify each term:
- For the first term: \[ \frac{56r}{4t} = \frac{56}{4} \cdot \frac{r}{t} = 14 \cdot \frac{r}{t} = \frac{14r}{t} \]
- For the second term: \[ \frac{12}{4t} = \frac{12}{4} \cdot \frac{1}{t} = 3 \cdot \frac{1}{t} = \frac{3}{t} \]
-
Combine the simplified terms: \[ \frac{14r}{t} - \frac{3}{t} \]
-
Since the terms have a common denominator of \( t \), we can combine them: \[ \frac{14r - 3}{t} \]
Thus, the simplified quotient of \( \frac{56r - 12}{4t} \) is: \[ \frac{14r - 3}{t} \]